Effects of nano-pore and macromolecule structure of coal samples on energy parameters variation during methane adsorption under different temperature and pressure. (1st April 2021) - Zhang, Junjian; Wei, Chongtao; Zhao, Chengjin; Zhang, Tao; Lu, Guanwen; Zou, Mingjun
Abstract: Research on methane adsorption in coal reservoirs by combining adsorption energy variation with molecular structure helps to explain the micro adsorption mechanism of methane. According to experimental data obtained from methane isothermal adsorption at different temperatures (20, 30 and 40 degrees centigrade) and pressure (0 ~ 10 MPa), effects of temperature and pressure on the energy parameters (adsorption potential, adsorption space, surface free energy and isosteric heat of adsorption) of middle and high rank coal samples were discussed from the angles of adsorption kinetics and thermodynamics. Moreover, pore and macromolecular structure of all the samples were elucidated by employing low temperature liquid nitrogen, carbon dioxide adsorption and infrared spectroscopy. Then, relationship between micro-pore structure, chemical structure parameters and adsorption energy variation were discussed. The following results has been achieved. 1) As adsorption pressure increases, reduction rate of surface free energy grows rapidly at the early period of lower pressure stage (0 ~ 8 MPa), then it becomes less than that of higher pressure stage (8 ~ 10 MPa). At the same adsorption pressure, reduction value rate of surface free energy decreases as coal rank increase. 2) Increasing temperature causes the decrease of adsorption capacity ( V L and P L ), and the sensitivity of temperature to adsorption capacity of high rank samples is stronger than that of middle rank samples. As R o, max increases, initial isosteric heat of adsorption gradually increases. 3) In contrast to meso -macropore, micro-pore is critical affecting adsorption capacity. Larger specific surface area and adsorption potential of micro-pore results in a decrease in the surface free energy. 4) When R o, max is less than 2.5%, the graphitization degree of aromatic increase linearly, and the length of the aliphatic chain reaches the minimum value. After that, macromolecule parameters varies smoothly. Then, functional groups variation affects the micro-pore structure evolution, whereas has a weak effect on the meso -macropore structure. Moreover, as apparent aromaticity ( fa ) increases, maximum surface free energy of coal sample increases linearly and the initial isosteric heat of adsorption increases exponentially, respectively. Above all, gas adsorption energy variation affects methane adsorption capacity, then it is also influenced by the micro-pore and internal chemical structure.